Technique of anaesthesia in pulmonary hypertension and thrombophilia in early pregnancy - Chuah, K.H.; Mansor, M.; Rajen, G.; Wang, C.Y.; Chan, Y.K. (Malaysian Medical Association, 2006)
Pulmonary hypertension in pregnancy is a rare condition but is associated with a high mortality. We report the case of a 29 year old female in early pregnancy with Protein C and S deficiency with recurrent deep venous thrombosis and pulmonary embolism and subsequent secondary pulmonary hypertension. The patient was counselled and consented for termination of pregnancy with tubal sterilization. She was administered continuous spinal anaesthesia with invasive monitoring. The successful anaesthetic management of this condition is described.